Effect of mindfulness-based interventions on students with mathematics anxiety: a discursive-analytic review - Vera Victor-Aigbodion (Universitas Negeri Padang, 2023)
Most students are affected by mathematics anxiety in terms of how they study, recall, and comprehend mathematical concepts. Mathematics anxiety significantly impedes students' efforts to attend or study mathematics courses. Researchers have developed mindfulness-based interventions (MBIs) to aid in the recovery of students suffering from academic anxiety, particularly mathematics anxiety. The primary objective of this article is to assess how effective these MBIs have aided in alleviating students from mathematics anxiety so as to achieve success in their academics. This study utilized a discursive-analytic literature review approach. The following MBIs were identified: mindfulness-based stress reduction (MBSR), mindfulness-based cognitive therapy (MBCT), dialectical behavioral therapy (DBT), self-compassion therapy (SCT), yoga, and meditation. Few studies examined some MBIs and reported their significant treatment effects on mathematics anxiety. Specifically, existing studies examining MBSR and MBCT for the treatment of mathematics anxiety in students reported a significant positive effect. A study examined the efficacy of SCT in treating mathematics anxiety in students and reported a positive effect. Educators who use MBIs should prioritize the implementation of successful therapy strategies with their students, consider the necessary time frame to achieve desired results, and explore the fundamental processes that facilitate change. This will facilitate future educators in adapting their techniques in a manner that is advantageous to their respective students.